ENHANCED STABILITY INVESTIGATION OF HIGH-GAIN BOOST CONVERTER FOR PHOTOVOLTAIC SYSTEM (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
An effective DC-DC converter is recommended for use in renewable energy applications, as suggested in the study. For the design of a high-gain boost converter (HGC), switched inductor cells (SIC) and voltage multiplier cells (VMC) are utilized. VMC provides high voltage gain in the converter side, while switched inductor cells provide a constant source current. Efficiency enables the recommended converter to maintain a high voltage gain at a low duty ratio. The converter stability is achieved under state space modelling (SSM). The electromagnetic compatibility (EMC) condition of the power converter is verified using a spectrum analyzer. The power semiconductor’s electrical discharge and potential energy under steady-state conditions, the Bode plot, and the Nyquist plot are examined. Furthermore, the interface of the PV module with a high-gain converter is simulated for the specified values.
Keywords: Photovoltaic (PV) module; High gain converter (HGC); Electromagnetic compatibility (EMC); Maximum power point tracking (MPPT); MATLAB